2009
DOI: 10.1159/000216541
|View full text |Cite
|
Sign up to set email alerts
|

Individual Differences in Behavioral, Physiological, and Genetic Sensitivities to Contexts: Implications for Development and Adaptation

Abstract: Although exposure to adversity places children at high risk for developmental problems, there is considerable variation in the adaptation of children exposed to both low and high levels of adversity. In recent years, researchers have made significant progress in understanding how social environments shape children’s development. Studies indicate that not all children are equally susceptible to environmental effects. In this article, we review the studies that examine individuals’ sensitivity to both positive a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(58 citation statements)
references
References 204 publications
3
53
0
Order By: Relevance
“…Discrepancies in findings between cross-sectional [52] and longitudinal [15, 40] stress reactivity studies underscore the need for additional prospective longitudinal research. Studies that include a developmentally-focused and process-oriented framework will be useful in gaining a greater understanding of the complex mechanisms of stress reactivity across development [38]. Furthermore, interactions among gender differences in physiological reactivity, contextual factors, and acute stressors should also be tested in longitudinal studies, as some reviews have indeed found gender differences in physiological responses among adolescents [62, 63].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Discrepancies in findings between cross-sectional [52] and longitudinal [15, 40] stress reactivity studies underscore the need for additional prospective longitudinal research. Studies that include a developmentally-focused and process-oriented framework will be useful in gaining a greater understanding of the complex mechanisms of stress reactivity across development [38]. Furthermore, interactions among gender differences in physiological reactivity, contextual factors, and acute stressors should also be tested in longitudinal studies, as some reviews have indeed found gender differences in physiological responses among adolescents [62, 63].…”
Section: Discussionmentioning
confidence: 99%
“…Rather, highly reactive individuals may be more susceptible to both positive (development-enhancing) and negative (risk-promoting) environments, as well as more responsive to interventions [36, 37]. For example, Boyce and Ellis suggested that children and adolescents may thrive more in positive and supportive contexts (e.g., cohesive family environment), but may also be more vulnerable to the adverse effects of negative contexts (e.g., chronic marital conflict, harsh parenting) [34, 35, 38]. In fact, several studies have found that a heightened stress response may be associated with maladaptive behaviors or adaptive functioning outcomes among youth [e.g., 5, 27, 34, 39, 40].…”
Section: Interactive Effects Of Stressful Family Life Events and Cortmentioning
confidence: 99%
“…There appears to be at least some evidence that heritable factors might influence the (self-) selection of potentially adverse environments (Kendler and Baker 2007;Vinkhuyzen et al 2009). Genes may also influence individual differences determining the response to an environmental event (Obradovic and Boyce 2009). Because of this, there has been a focus on examining potential heritable contributions to both PTSD and its neuroendocrinology, even to the extent that these relationships might be mediated by ELS (Heim et al 2009;Koenen et al 2009).…”
Section: Are Genetics Involved In Els or Ptsd?mentioning
confidence: 99%
“…Developmental theorists have proposed that psychophysiological factors may help to explain the variability in youths' vulnerability to negative environments (Obradović & Boyce, 2009;Steinberg & Avenevoli, 2000). Psychophysiological reactivity to stress, and autonomic reactivity in particular, has been highlighted as a likely moderator of links between aspects of the family environment and youth adjustment (El-Sheikh & Erath, 2011;Obradović, 2012).…”
Section: The Moderating Role Of Sclrmentioning
confidence: 99%